A Sociologia vai ao cinema: o uso de audiovisual como recurso didático na aula de Sociologia - Rocha, Fernanda de Lemos (2020)
In the midst of the current, technological culture, full of information and images, one can perceive the increasing difficulty of attention and concentration of young people inside and outside the school context, in this sense in relation to students, the implementation of differentiated pedagogical tools they can be an alternative for knowledge to become more interesting and meaningful. The objective of the present work is to investigate the use of audiovisual as a didactic resource in Sociology classes in High School, understanding to what extent, a class with the use of audiovisual can facilitate or enhance the use of the youngster's cultural capital, managing to expand the power interpretation of social reality, denaturalization and creation of new knowledge standards. This is the description of the research carried out in high schools in Ceará, between the years 2018 and 2020, developed during the Professional Master of Sociology in the National Network (PROFSOCIO) of the Federal University of Ceará, the inspiration of this investigation part the creation of a Sociology discipline mediated exclusively by audiovisuals, entitled: Sociology Goes to Cinema. As for the methodology for the production of this, a bibliographic study was carried out taking as theoretical references Bourdieu (1999), Napolitano (2003), Santaella (2012), Morin (2014), among others, seeking to understand to what extent the use of audiovisuals in the room classroom enhances the teaching-learning process. Investigative techniques, participant observation, interviews with teachers, questionnaires and a focus group with students were also implemented. It should be noted that the Professional Master of Sociology enables and guides the construction of a final research product, so I opted for the formulation of a catalog with audiovisuals and indication of didactic strategies to explore them, that is, pedagogical material to provide guidance practical and objective to the professor of Sociology or related disciplines.